SPTBN1 overexpression ameliorates atherosclerosis by inhibiting oxidative stress and inflammation via regulating the TRIM37/TRAF2/NF-κB pathway - Senyan Wu; Xiaoni Tan; Guobing Cheng (European Journal of Medical Research)
Abstract Background Endothelial cell apoptosis and oxidative stress are pivotal drivers of atherosclerosis (AS) progression. It was revealed that spectrin beta, non-erythrocytic 1 (SPTBN1) levels were remarkably decreased in the atherosclerotic plaque vessels of advanced lesions. This study aimed to elucidate the roles of SPTBN1 in endothelial dysfunction during AS progression. Methods SPTBN1 levels in the plasma samples of AS patients and aortic tissues of AS mouse model were tested. Human umbilical vein endothelial cells (HUVECs) were stimulated with oxidized low-density lipoprotein (ox-LDL) to mimic atherosclerotic conditions. After transfection of SPTBN1 overexpression plasmids, cell viability, apoptosis, oxidative stress marker including reactive oxygen species (ROS), malondialdehyde (MDA), and superoxide dismutase (SOD), and inflammatory molecules including vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) were examined. Then, the interaction of SPTBN1 and methyltransferase-like 14 (METTL14) was examined using co-immunoprecipitation assay. The m6A methylation level of tripartite motif-containing 37 (TRIM37) was determined using methylated RNA immunoprecipitation-qPCR (MeRIP-qPCR). Additionally, the effects of SPTBN1 overexpression on atherosclerotic plaque formation were assessed in a high-fat diet-induced AS mouse model. Results SPTBN1 was downregulated in plasma samples of AS patients andaortic tissues of AS mouse model. SPTBN1 overexpression suppressed apoptosis, oxidative stress, and inflammation in ox-LDL-treated HUVECs. Mechanistically, SPTBN1 inhibited TRIM37 expression by promoting METTL14-mediated TRIM37 m6A methylation. TRIM37 overexpression abolished the protective effects of SPTBN1 on ox-LDL-treated HUVECs. TRIM37 promoted K63-linked ubiquitination of tumor necrosis factor receptor-associated factor 2 (TRAF2) and activated the NF-κB pathway in HUVECs. Furthermore, SPTBN1 overexpression alleviated atherosclerotic plaque formation, arterial lesions and inflammation in AS mice. Conclusion SPTBN1 overexpression suppressed apoptosis, oxidative stress, and inflammation in ox-LDL-treated HUVECs by regulating the TRIM37/TRAF2/NF-κB pathway, thereby inhibiting AS development in mice. Our findings advance understanding of the molecular basis of endothelial homeostasis and identify a potential therapeutic target for AS.